Fatty acid profile and meat quality of young bulls fed ground soybean or ground cottonseed and vitamin E - Machado Neto, Otávio Rodrigues[UNESP]; Chizzotti, Mário Luiz; Ramos, Eduardo Mendes; Oliveira, Dalton Mendes de; Lanna, Dante Pazzanese Duarte; Ribeiro, Julimar do Sacramento; Lopes, Leandro Sâmia; Descalzo, Adriana Maria; Amorim, Tamyres Rodrigues de; Ladeira, Márcio Machado (Cambridge Univ Press, 2015)
The objective of this study was to evaluate the fatty acid profile and qualitative characteristics of meat from feedlot young bulls fed ground soybean or ground cottonseed, with or without supplementation of vitamin E. A total of 40 Red Norte young bulls, with an initial average age of 20 months, and an initial average BW of 339 +/- 15 kg, were allotted in a completely randomized design using a 2 x 2 factorial arrangement, with two oilseeds, and daily supplementation or not of 2500 IU of vitamin E. The experimental period was for 84 days, which was preceded by an adaptation period of 28 days. The treatments were ground soybean (SB), ground soybean plus vitamin E (SBE), ground cottonseed (CS) and ground cottonseed plus vitamin E (CSE). The percentage of cottonseed and soybean in the diets (dry matter basis) was 24% and 20%, respectively. Diets were isonitrogenous (13% CP) and presented similar amount of ether extract (6.5%). The animals were slaughtered at average live weight of 464 +/- 15 kg, and samples were taken from the longissimus dorsi muscle for the measurement of fatty acid concentration and the evaluation of lipid oxidation and color of the beef. Before fatty acid extraction, muscle tissue and subcutaneous fat of the longissimus dorsi were separated to analyze fatty acid profile in both tissues. Supplementation of vitamin E did not affect fatty acid concentration, lipid oxidation and color (P > 0.05). Subcutaneous fat from animals fed CS diet had greater C12: 0, C16: 0 and C18: 0 contents (P < 0.03). In addition, CS diets reduced the C18: 1 and C18: 2 cis-9, trans-11 contents in subcutaneous fat (P < 0.05). The muscle from animals fed CS tended to higher C16: 0 and C18: 0 contents (P < 0.11), and decreased C18: 1, C18: 2 cis-9, trans-11 and C18: 3 contents (P < 0.05) compared with SB. The Delta(9)-desaturase index was greater in muscle from animals fed SB (P < 0.01). At 42 days of age, meat from cattle fed SB had a greater lipid oxidation rate (P < 0.05). Meat from animals fed SB diets had less lightness and redness indices than meat from animals fed CS diets after 14 days of age. In conclusion, the addition of ground cottonseed in the finishing diets did increase the saturated fatty acid content of the longissimus dorsi. However, animals fed cottonseed exhibited greater lightness and redness of beef. In this study, the addition of vitamin E did not affect qualitative characteristics of meat.
Keywords: Beef; CLA; Lipids; Oilseeds; Tocopherol